Orsaker till trombocytopeni hos hund - Tomaszewski, Åsa (2005)
The purpose of this retrospective case study was to determine which diseases are associated with thrombocytopenia in Swedish dogs. Records of 123 dogs with thrombocytopenia were evaluated. The most common cause was neoplasia-associated thrombocytopenia (32%). The largest proportion within this group was unspecified neoplasia. The second most common cause was infectious or inflammatory disease (26%). The most common diagnosis within this category was Ehrlichiosis. The third largest category was comprised of immunemediated diseases (15%). These were followed by non-inflammatory diseases (12%), depression of the bone marrow or anemia (6%), drug-induced thrombocytopenia or toxicity (5%), DIC (2%) and miscellaneous causes (2%).